2023
DOI: 10.1186/s12993-022-00199-z
|View full text |Cite
|
Sign up to set email alerts
|

Previous experience with delays affects delay discounting in animal model of ADHD

Abstract: Background ADHD is a disorder where a common symptom is impulsive behaviour, a broad term associated with making sub-optimal choices. One frequently used method to investigate impulsive behaviour is delay discounting, which involves choosing between a small, immediate reinforcer and a delayed, larger one. Choosing the small immediate reinforcer is by itself, however, not sufficient for terming the choice impulsive, as all organisms eventually switch to choosing the small, immediate reinforcer w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Based on these studies and our current work, we hypothesize that females will show higher choice impulsivity and PNNs densities in the mPFC compared to males after ISD. Second, previous work has shown that increases in delay discounting behavior depend on the order in which delays are presented and/or reward-related cues 29 , 54 , 66 , 67 . Regarding delay presentation, some studies have shown that the administration of amphetamine increases or decreases discounting behavior depending on the order of delay presentation 54 , 66 , and suggest that the effects of amphetamine reflect perseveration and not intertemporal decision-making deficits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these studies and our current work, we hypothesize that females will show higher choice impulsivity and PNNs densities in the mPFC compared to males after ISD. Second, previous work has shown that increases in delay discounting behavior depend on the order in which delays are presented and/or reward-related cues 29 , 54 , 66 , 67 . Regarding delay presentation, some studies have shown that the administration of amphetamine increases or decreases discounting behavior depending on the order of delay presentation 54 , 66 , and suggest that the effects of amphetamine reflect perseveration and not intertemporal decision-making deficits.…”
Section: Discussionmentioning
confidence: 99%
“…Second, previous work has shown that increases in delay discounting behavior depend on the order in which delays are presented and/or reward-related cues 29 , 54 , 66 , 67 . Regarding delay presentation, some studies have shown that the administration of amphetamine increases or decreases discounting behavior depending on the order of delay presentation 54 , 66 , and suggest that the effects of amphetamine reflect perseveration and not intertemporal decision-making deficits. Our results show that ISD increases discounting with increasing delays, which is the opposite of what was expected to be found if stressed animals persevere with a given response.…”
Section: Discussionmentioning
confidence: 99%
“…Given the differences between strains in the timing task from Experiment 1, we predicted that we would observe differences in the delay-discounting task where response consequences are distributed in time, and thus, temporal processing may play a critical role. There has been a fairly substantial amount of work assessing impulsive choice in SHR/NCrl rats using a delay-discounting paradigm, and most of that work has found SHR/NCrl rats to be more impulsive than controls (Aparicio et al, 2019(Aparicio et al, , 2020Bizot et al, 2007;Fox et al, 2008;Hand et al, 2009;Orduña, 2015;Orduña & Mercado, 2017;Sanabria & Killeen, 2008;Sjoberg et al, 2023;Sutherland et al, 2009;Wooters & Bardo, 2011); however, very little work has included an outbred control strain like the WI strain. This is particularly important given the probable inadequacies of the WKY/NCrl strain to serve as a control for SHR/NCrl (Alsop, 2007;Sagvolden et al, 2009), and some mixed findings when SHR/NCrl and WKY/NCrl are compared (Adriani et al, 2003;Garcia & Kirkpatrick, 2013;González-Barriga & Orduña, 2022).…”
Section: Experiments 2: Delay Discounting In Shr/ncrl Wky/ncrl and Wi...mentioning
confidence: 99%
“…We had mice first undergo “Worsening” and then “Improving” versions of delay and probability discounting because the acclimation to an Improving schedule (i.e. going from no delay training to large delay testing) can obscure sensitivity to delay in models of neurodevelopmental disorders (Sjoberg et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…We had mice first undergo "Worsening" and then "Improving" versions of delay and probability discounting because the acclimation to an Improving schedule (i.e. going from no delay training to large delay testing) can obscure sensitivity to delay in models of neurodevelopmental disorders (Sjoberg et al, 2023). Each schedule promotes a different choice pattern, which gives us the ability to compare whether delay or risk orientation alters choice in 16p11.2 hemideletion mice.…”
Section: Introductionmentioning
confidence: 99%